MODERN TENDENCIES OF EDUCATION COMMUNICATION IN THE CONTEXT OF TRANSITION TO A SMART SOCIETY (Scientific journal of the Fergana State University, 2023)
In this article, in the context of the information society, orientation to the use of innovative technologies using information and communication technologies (ICT) in the professional activities of future teachers in the educational system, effective professional cooperation, ready to take into account the individual characteristics of each student to the maximum extent, the importance of sharing advanced pedagogical experience was mentioned.